Detection and imaging via time reversal signal processing method - Lin, Lu. (2010)
Target embedded in medium detection and location imaging is an important research topic in domains such as medical imaging, metal destructive testing and military purpose area target imaging. In this project, the performance of the combination between time reversal technique and traditional imaging methods are studied. The time reversal signal processing method indicates that the echo signal is sampled, digitized, stored, time-reversed and then retransmitted. Then the returned signal is processed by the conventional imaging algorithms to produce the target images. From that, we compare the performance between the Multiple Signal Classification (MUSIC) method and Time Reversal MUSIC (TR-MUSIC) method. Besides, we also compare the performance between Synthetic Aperture Radar (SAR) and Time Reversal SAR (TR-SAR) algorithm in this project. MUSIC algorithm is an eigen-structure based method for signal arrival direction finding. In the time reversal MUSIC method, time reversal processing is applied before executing the MUSIC algorithm. Time reversal technique saves much computational consumption. And it also makes the MUSIC work for well-resolved and non-well-resolved targets. But TR-MUSIC method is sensitive to the noise. In the simulation we add different amount uncorrelated noise to the signal, and test threshold of signal to noise ratio when TR-MUSIC algorithm can perform well.